Elucidating the structure, and composition of bacterial symbionts in the gut regions of wood-feeding termite, Coptotermes formosanus and their functional profile towards lignocellulolytic systems - Dar, Mudasir A.; Xie, Rongrong; Jing, Luohui; Qing, Xu; Ali, Shehbaz; Pandit, Radhakrishna S.; Shaha, Chaitali M.; Sun, Jianzhong (Frontiers in Microbiology, 2024)
The wood-feeding termite, Coptotermes formosanus, presents an efficient lignocellulolytic system, offering a distinctive model for the exploration of host-microbial symbiosis towards lignocellulose degradation. Despite decades of investigation, understanding the diversity, community structure, and functional profiles of bacterial symbionts within specific gut regions, particularly the foregut and midgut of C. formosanus, remains largely elusive. In light of this knowledge gap, our efforts focused on elucidating the diversity, community composition and functions of symbiotic bacteria inhabiting the foregut, midgut, and hindgut of C. formosanus via metagenomics. The termite harbored a diverse community of bacterial symbionts encompassing 352 genera and 26 known phyla, exhibiting an uneven distribution across gut regions. Notably, the hindgut displayed a higher relative abundance of phyla such as Bacteroidetes (56.9%) and Spirochetes (23.3%). In contrast, the foregut and midgut were predominantly occupied by Proteobacteria (28.9%) and Firmicutes (21.2%) after Bacteroidetes. The foregut harbored unique phyla like Candidate phylum_TM6 and Armatimonadetes. At the family level, Porphyromonadaceae (28.1%, 40.6%, and 53.5% abundance in foregut, midgut, and hindgut, respectively) and Spirochaetaceae (foregut=9%, midgut=16%, hindgut=21.6%) emerged as dominant families in the termite's gut regions.Enriched operational taxonomic units (OTUs) were most abundant in the foregut (28), followed by the hindgut (14), while the midgut exhibited enrichment of only two OTUs. Furthermore, the functional analyses revealed distinct influences of bacterial symbionts on various metabolic pathways, particularly carbohydrate and energy metabolisms of the host. Overall, these results underscore significant variations in the structure of the bacterial community among different gut regions of C. formosanus, suggesting unique functional roles of specific bacteria, thereby inspiring further investigations to resolve the crosstalk between host and microbiomes in individual gut-regions of the termite.